2022
DOI: 10.3389/fimmu.2022.888250
|View full text |Cite
|
Sign up to set email alerts
|

Aberrantly Activated APOBEC3B Is Associated With Mutant p53-Driven Refractory/Relapsed Diffuse Large B-Cell Lymphoma

Abstract: Tumor protein 53 (TP53) mutation predicts an unfavorable prognosis in diffuse large B-cell lymphoma (DLBCL), but the molecular basis for this association remains unclear. In several malignancies, the cytidine deaminase apolipoprotein B mRNA editing enzyme catalytic subunit 3B (APOBEC3B) has been reported to be associated with the TP53 G/C-to-A/T mutation. Here, we show that the frequency of this mutation was significantly higher in relapsed/refractory (R/R) than in non-R/R DLBCL, which was positively associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…For instance, based on a human cancer gene list, 52 individual CAG-A3B tumors reported here have APOBEC3 signature mutations in several established cancer genes including Apc (Glu2182Lys) and Plcg1 (Glu1163Lys), as well as APOBEC3-associated events in other cancer genes such as a frameshift mutation in a TC motif in Nf2 (Glu541fs). Surprisingly, despite multiple studies associating p53 loss of function in A3B mutagenesis, 42 , 53 , 54 , 55 no mutations or copy-number variations are evident thus far in Trp53 in CAG-A3B tumor genomes.…”
Section: Discussionmentioning
confidence: 94%
“…For instance, based on a human cancer gene list, 52 individual CAG-A3B tumors reported here have APOBEC3 signature mutations in several established cancer genes including Apc (Glu2182Lys) and Plcg1 (Glu1163Lys), as well as APOBEC3-associated events in other cancer genes such as a frameshift mutation in a TC motif in Nf2 (Glu541fs). Surprisingly, despite multiple studies associating p53 loss of function in A3B mutagenesis, 42 , 53 , 54 , 55 no mutations or copy-number variations are evident thus far in Trp53 in CAG-A3B tumor genomes.…”
Section: Discussionmentioning
confidence: 94%
“…Mounting evidence demonstrates that A3B is clinically significant in cancer. A3B overexpression was shown to confer resistance to drugs such as doxorubicin and tamoxifen [ 44 , 45 ]. But on the other hand, A3B may enhance the sensitivity to immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…The intron numbers in Pvul-KCS genes range from 0 to 2. It was observed that there were no intron regions in Pvul-KCS genes except Pvul- In their study, Zhang et al (2022) demonstrated that the 25 SbKCS genes exhibited a range of intron counts, spanning from 0 to 1. Lian et al (2020) showed that KCS genes within the same subgroup exhibited similar exon-intron distribution.…”
Section: Interspecific Phylogenetic Analysis Of Pvul-kcs Proteins Con...mentioning
confidence: 96%
“…In their study, Zhang et al (2022) observed that 25 SbKCS genes detected in the phylogenetic tree classification of Sorghum bicolor were divided into 5 groups with A. thaliana, Oryza sativa, Zea mays and Brochypodium distachyon. Lian et al (2020) observed that the 28 MdKCS genes identified in the phylogenetic tree classification of apple fruit (Malus domestica) were divided into 4 groups with A. thaliana and that there was a close relationship between different domains of KCS-related genes (KCS1-like, FAE1-like, FDHlike and CER6).…”
Section: Interspecific Phylogenetic Analysis Of Pvul-kcs Proteins Con...mentioning
confidence: 99%